Covalent organic frameworks for photocatalytic applications - Yang, Qing; Luo, Maolan; Liu, Kewei; Cao, Hongmei; Yan, Hongjian (Applied catalysis. B, Environmental, 2020)
[Display omitted] •The COFs photocatalysts were reviewed according to the classification of building blocks.•The principle for designing photocatalytic active COFs were summarized.•The method for synthesis COFs were reviewed.•The potential photocatalytic applications were discussed. Semiconductor photocatalysts are the main platform and play an essential role in photocatalysis. In recent years, covalent organic frameworks (COFs) materials have attracted extensive research interest. COFs feature periodic organic units, high thermal and chemical stability, high porosity, large surface area, π-conjugated structure and π-π stacking layers, as well as broad visible-light absorption range and high charge separation efficiency. Furthermore, the band structure of COFs can be rationally tuned by integrating different molecular building blocks with appropriate linkage, constructing π-conjugated system and introducing electron donor-acceptor units into the conjugated framework. These unique properties make COFs promising in photocatalytic water splitting, dye degradation, CO2 reduction, and organic transformation, etc. In this review, the research progress on COF photocatalysts were discussed, including the principles for designing photocatalytic active COFs, the synthetic methods, the classification of COFs based on the building blocks, and their potential applications in photocatalysis field.